Conductive Polymer Work Function Changes due to Residual Water: Impact of Temperature‐Dependent Dielectric Constant. (11th September 2020) - Mansour, Ahmed E.; Kim, Hongwon; Park, Soohyung; Schultz, Thorsten; Cao, David Xi; Nguyen, Thuc‐Quyen; Brütting, Wolfgang; Opitz, Andreas; Koch, Norbert
Abstract: Solution‐processed conducting polymer thin films are key components in organic and flexible electronic and optoelectronic devices. An archetypal conducting polymer is poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS), which can feature a high work function and thus helps achieving Ohmic contacts for holes with many semiconductors. However, it is known that residual water in PEDOT:PSS films lowers their work function and is detrimental for device lifetime. Our photoelectron spectroscopy experiments reveal that the work function of PEDOT:PSS films containing residual water shows the same trend as function of temperature as does the dielectric constant (ε) of water, in the range between 25 °C and ‐100 °C. Consistently, it is found from impedance spectroscopy measurements that ε of residual water containing PEDOT:PSS films increases with decreasing temperature. After removal of residual water from PEDOT:PSS films by annealing in ultrahigh vacuum, the work function of thin films is much higher than before (reaching 6.1 eV) and, notably, independent of temperature. In contrast, no indication is found that the presence of residual water has any impact on the electrical conductivity. For a nominally water‐free molecularly doped conjugated donor/acceptor copolymer films, a correlation between sample work function and temperature similar to those seen for PEDOT:PSS is found. Abstract : Residual water in conductive polymer films leads to a temperature‐dependent dielectric constant. This, in turn, results in a pronounced temperature dependence of the polymer work function, which decreases with decreasing temperature. Removal of residual water by annealing maximizes the work function and makes it independent of temperature.